Role of Protein Kinase C in Podocytes and Development of Glomerular Damage in Diabetic Nephropathy - Teng, Beina; Duong, Michelle; Tossidou, Irini; Yu, Xuejiao; Schiffer, Mario (Frontiers in Endocrinology, 2014)
The early glomerular changes in diabetes include a podocyte phenotype with loss of slit diaphragm proteins, changes in the actin cytoskeleton and foot process architecture. This review focusses on the role of the Protein Kinase C family in podocytes and points out the differential roles of classical, novel and atypical PKCs in podocytes. Some PKC-isoforms are indispensable for proper glomerular development and slit diaphragm maintenance whereas others might be harmful when activated in the diabetic milieu. Therefore some might be interesting treatment targets in the early phase of diabetes.